Impact of Supplement Diets on Flights of Cross Breed Honeybee (Apis mellifera L.) - Thapa, RB; Pokhrel, S (Journal of the Institute of Agriculture and Animal Science, 2005)
An experiment was conducted to evaluate the response of supplement diets on flight activities of cross breed honeybee (Apis mellifera Lin.) in Chitwan, Nepal. The experiment consisted of five replications and four feeding treatments: feeding low dose sugar (syrup of 166 g sugar); feeding high dose sugar (syrup of 333 g sugar); feeding modified diet (syrup of 166 g sugar + 30 g pollen substitute); and control (no diet supplement except 250 g sugar honey candy to prevent from starvation). Each hive (replication) consisted of five-framed A. mellifera colony, which were fed for six days with four days breaks in each feeding and altogether eleven feedings were provided. Sugar syrup feeding stimulated bee foragers flights by 908-987% out-going and 578-704% in-coming, respectively. Modified diet (low dose sugar syrup combined with pollen substitute) was suitable for off-season management of honeybee colonies, which supported high rate of flight activities i.e. 3.3 times out-going and 2.8 times in-coming as compared to the control colonies. Other treatments were intermediate types. The combined diet also showed higher flights than feeding low dose sugar syrup alone indicating necessity of feeding appropriate diet during off-season under Chitwan condition for good flight and foraging activities of honeybees. Key words: Pollen substitutes, sugar syrup/sugar-honey candy, out-going, in-coming, cross breed J. Inst. Agric. Anim. Sci. 26:71-76 (2005)